Association of Diabetes Duration and Diabetes Treatment with the Risk of Hepatocellular Carcinoma - Hassan, Manal (2010)
BACKGROUND: Despite the observed association between diabetes mellitus and hepatocellular carcinoma (HCC), little is known about the effect of diabetes duration before HCC diagnosis and whether some diabetes medications reduced the risk of HCC development. This objective of the current study was to determine the association between HCC risk and diabetes duration and type of diabetes treatment. METHODS: A total of 420 patients with HCC and 1104 healthy controls were enrolled in an ongoing hospital-based case-control study. Multivariate logistic regression models were used to adjust for HCC risk factors. RESULTS: The prevalence of diabetes mellitus was 33.3% in patients with HCC and 10.4% in the control group, yielding an adjusted odds ratio (AOR) of 4.2 (95% confidence interval [95% CI], 3.0-5.9). In 87% of cases, diabetes was present before the diagnosis of HCC, yielding an AOR of 4.4 (95% CI, 3.0- 6.3). Compared with patients with a diabetes duration of 2 to 5 years, the estimated AORs for those with a diabetes duration of 6 to 10 years and those with a diabetes duration >10 years were 1.8 (95% CI, 0.8-4.1) and 2.2 (95% CI, 1.2- 4.8), respectively. With respect to diabetes treatment, the AORs were 0.3 (95% CI, 0.2-0.6), 0.3 (95% CI, 0.1-0.7), 7.1 (95% CI, 2.9-16.9), 1.9 (95% CI, 0.8-4.6), and 7.8 (95% CI, 1.5-40.0) for those treated with biguanides, thiazolidinediones, sulfonylureas, insulin, and dietary control, respectively. CONCLUSIONS: Diabetes appears to increase the risk of HCC, and such risk is correlated with a long duration of diabetes. Relying on dietary control and treatment with sulfonylureas or insulin were found to confer the highest magnitude of HCC risk, whereas treatment with biguanides or thiazolidinediones was associated with a 70% HCC risk reduction among diabetics. Cancer 2010;116:1938–46. VC 2010 American Cancer Society